IMPLEMENTATION OF CUSTOMER RELATIONSHIP MANAGEMENT (CRM) IN EFFORTS TO IMPROVE CUSTOMER LOYALTY AT BANK SUMUT KCP SYARIAH HM YAMIN MEDAN - Bunga Artha Nefia Efendi; Juliana Nasution; Nursantri Yanti (Indonesian Journal of Business and Management, 2026)
This study aims to analyze the implementation of Customer Relationship Management (CRM) and identify the obstacles encountered in its application to enhance customer loyalty at Bank Sumut KCP Syariah HM Yamin Medan. The study was motivated by the increasing importance of customer relationship strategies in the Islamic banking industry and the limited qualitative evidence regarding CRM implementation in regional Islamic banking institutions. A descriptive qualitative approach was employed, with data collected through in-depth interviews, observations, and documentation. Eight informants were purposively selected, consisting of three employees and five customers. Data were analyzed using the interactive model of data reduction, data display, and conclusion drawing, while data validity was ensured through source triangulation, technique triangulation, and member checking. The findings reveal that CRM implementation has been carried out through three main dimensions, namely people, process, and technology. The people dimension is reflected in responsive, friendly, and empathetic services provided by employees. The process dimension is implemented through customer identification, differentiation, interaction, and service customization activities. The technology dimension is supported by the utilization of mobile banking, internet banking, QRIS, and auto-debit facilities to improve service accessibility and efficiency. However, CRM implementation remains constrained by the absence of an integrated CRM system and limitations in human resources for conducting systematic customer relationship activities. The study concludes that effective integration of people, process, and technology contributes to strengthening customer relationships and enhancing customer loyalty. These findings provide practical insights for Islamic banking institutions seeking to improve customer relationship strategies and maintain sustainable customer loyalty in an increasingly competitive banking environment.